(untitled) (Medico Legal Update, 2021)
Objective: To assess maternal serum amyloid A (SAA) levels among women with primary unexplained recurrent missed miscarriages. Patients and Method: A prospective study (case control study) in Al-Zahraa Maternity Hospital, Najaf, Iraq, from first of January to the first of December of 2019 the study was conducted among 91 who were divided into two groups: 1. Group 1: Patient with miscarriage in the early trimester with at least two consecutive primary unexplained REPLs and no previous live births were enrolled. 2. Group 2: A control group was formed of women with miscarriage no history of REPL who had at least one previous uneventful pregnancy with no adverse outcomes. Serum samples were collected to measure SAA levels. The main outcome was the association between SAA and primary unexplained REPL. A total number of 91 participants. Mean SAA level increased in women with early missed abortion than those women in the control group (p<0.001). The level of SAA was dependent indicator of primary unexplained REPL, (p<o.oo1). found that serum amyloid Alevel in women with missed miscarriages represent as biomarker of this complication of pregnancy. Conclusions: Serum amyloid A theoretically a promising marker that prompts further study for primary unexplained missed miscarriage. in the Studies may be performed, for example, measurement of SAA level in women with history of early recurrent missed abortion during pregnancy and before and also compare SAA levels in women with non-pregnant state Such studies may direct the timing for initiating new therapies the future.